PERLINDUNGAN HUKUM TERHADAP KONSUMEN AKIBAT DUGAAN MANIPULASI IKLAN PELAKU USAHA BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Zakaria Rasyid; Ermanto Fahamsyah (Fakultas Hukum Universitas Tarumanagara, 2019)
This study aims to find out and analyze consumer protection. Manipulating advertisements carried out by companies based on Law Number 8 of 1999 Concerning Consumer Protection (case study of sweetened condensed milk). The research method in the discussion of this Thesis is normative research, that is research conducted to study the legal forms against consumers which are suspected of being manipulation of advertisements carried out by business actors based on Law Number 8 of 1999 Concerning Consumer Protection. Related to the issues discussed in this study concerning legal protection to consumers, the alleged manipulation of advertisements carried out by companies attempts based on Law No. 8 of 1999 concerning Consumer Protection.